ANALISIS BREAK EVEN POINT USAHA PENGRAJIN GULA MERAH DI DESA SEPARE KECAMATAN LOANO KABUPATEN PURWOREJO - Nurlaila Fatmawati (Jurnal Agroteknologi (Agronu), 2022)
Break Even Point (BEP) Analysis is a technical analysis that learn the relationship between fixed costs, variable costs, profits and activity volume. The concept of Break Even analysis can help brown sugar craftsmen in planning profits and controlling business activities so that losses can be minimized. Brown sugar craftsmen can find out the volume of production/sales that must be achieved and the selling price that must be set so that they break even or do not lose or make no profit. The purpose of this study was to find out  (1) the amount of production costs, revenue, income and profits of brown sugar craftsmen in Separe Village, Loano. (2) the amount of Break Even Point (BEP) production and Break Even Point (BEP) The prices on brown sugar craftsmen business in Separe Village, Loano District. The research sample was taken by accidental sampling on 30 respondents. The results showed that (1) the amount of production costs incurred was Rp. 7,067,304.17/5 months, the revenue earned was Rp. 7,602,578,93/5 months, the income received was Rp. 6,196,628,93/5 months. as well as the business profit of brown sugar craftsmen in Separe Village, Loano District of Rp. 535,274.76/5 months (2) Break Even Point (BEP) production of brown sugar craftsmen in Separe Village, Loano District is 514.29 kg and Break Even Point (BEP) price is 12774.16 per kg Keywords : brown sugar, cost, income, profit, Break Even Point